Treatment of patients with acute coronary syndrome and atrial fibrillation - Fedia, Ben Salem (ScienceRise: Medical Science, 2019)
The aim was to study the possible protective effect of drug therapy regarding the development of AF in patients with ACS and compliance with the standards of treatment of these patients in everyday clinical practice. Materials and research methods. A study was conducted of 125 patients with ACS who were hospitalized with ACS to the center of percutaneous coronary interventions of the KNP of the Kharkiv Regional Council "Regional Clinical Hospital" for four years from 2015-2018, among which 65 had atrial fibrillation . The criterion for inclusion in the study was the presence of ACS; exclusion criteria were the presence of severe concomitant diseases (active oncological processes, chronic IV degree renal failure, etc.), heart defects, and the patient’s refusal to participate in the study. In accordance with the Helsinki Declaration, all patients were informed about the aim, methods and design of the study and gave their consent to participate. Patients were divided into groups according to the presence of AF. In group 1, patients with AF were combined, and patients who had AF for the first time during hospitalization for ACS were subgroup 1a (n=41); patients in whom AF was observed before the development of ACS were subgroup 1b (n=24). The second group consisted of patients without indications of AF in the history and during hospitalization (n=60). Results. The majority of patients of the 1st group, namely, 92.3 %, had three or more points on the CHA2DS2-VASc scale of thromboembolic complications, while the greatest number of patients (n=41, 63 %) with ACS and AF were 4-5 points on the scale of risk of thromboembolic complications according to CHA2DS2-VASc. Most patients had a score of 0-1 on the bleeding risk scale. When evaluating drug therapy in patients with ACS, it was found that acetylsalicylic acid was administered to almost all patients with ACS, except for patients with concomitant bronchial asthma. The majority of patients with ACS, with or without concomitant AF, received clopidogrel as a double antiplatelet therapy along with acetylsalicylic acid. Anticoagulant therapy with the use of warfarin and new oral anticoagulants was more often prescribed to patients with 1b subgroups. Calcium antagonists were more frequently prescribed in patients of the 2nd group compared with the 1st (n1=4; 6.2 % vs n2=12; 20.0 %, p=0.0228). Statins were administered to hospitals in almost all patients, except for a few patients with intact coronary vessels. Prehospital administration of the loading dose of the P2Y12 inhibitor was more frequently recorded in the 1st group of patients as compared with the 2nd (n1=26; 40.0 % vs n2=13; 21.7 %, p=0.0292), at the same time among patients with 1a-subgroups with AF, which appeared for the first time, a significantly rarer prescription of the pre-hospital loading dose of the P2Y12 inhibitor was observed compared with the 1b-subgroup (n1a=11; 26.8 % vs n1b=15; 62.5 %, p=0 , 0061). The majority of patients in all groups received ACE inhibitors / ARBs in basic therapy during the hospital period. The prescription of diuretics was more often registered among patients of the 1b-subgroup, which indicates a more severe course of CHF in this group of patients, which preceded the development of ACS. An increase in the frequency of triple therapy prescriptions among patients with AF over the years 2015-2018 was found, which corresponds to the existing modern standards of medical care regarding the appointment of combination anticoagulant and anti-platelet therapy to patients with AF and ACS. Unassigned triple therapy in the group of patients with AF, which originated for the first time, is associated with a greater frequency of registration of anemia in this group of patients. Conclusion. In accordance with the results of the study, all patients with ACS and AF have a high thromboembolic risk and require anti-coagulant therapy. In everyday clinical practice, in the discharge of patients with ACS and AF from hospital more than a third (38.1 %) patients are not recommended anticoagulant therapy, which does not comply with current recommendations. At the same time, patients are more often prescribed therapy who had AF before the development of ACS, while patients in subgroup 1a who have AF demonstrated in the acute period have less than half. In a retrospective analysis of extracts of case histories over the period 2015-2018, an increase in the frequency of triple therapy prescriptions among patients with AF was found. The most common cause of non-prescribing anticoagulants is anemia and a high risk of bleeding.